Feasibility of lung ultrasound for locating bronchial blockers in pediatric thoracic surgery: a retrospective analysis - Weiwei Cai; Yuting Song; Wei Gu; Huanhuan Ni; Huiying Shao; Hongqiang Huang (BMC Anesthesiology)
Abstract Objective To identify the feasibility of using lung ultrasound to determine the position of bronchial blockers in pediatric patients. Methods In this study, children aged 4–8 years who underwent elective right one-lung ventilation at our hospital between January 2019 and August 2022 were selected. We collected the results of lung ultrasound and fiberoptic bronchoscopy during the placement of bronchial blockers in these children. The accuracy, sensitivity, and specificity of lung ultrasound in determining the position of bronchial blockers were calculated. Additionally, the reproducibility of lung ultrasound in determining the appropriateness of bronchial blockers was also calculated. Furthermore, information regarding whether there were complications associated with lung ultrasound examination or fiberoptic bronchoscopy was also collected. Results The accuracy of lung ultrasound for determining the position of bronchial blockers was 95.0%. When the position of BBs was appropriate, the sensitivity of lung ultrasound was 96.3% and the specificity was 88.9%. When the position of BBs was too shallow, the sensitivity of lung ultrasound was 75% and the specificity was 96.7%. The reproducibility test of lung ultrasound for determining the position of bronchial blockers had a weighted kappa value of 0.91, P < 0.001. In this study we found 6 children had hypoxemia and 6 children had airway mucosal bleeding during fiberoptic bronchoscopy. And no complications linked to lung ultrasound examination were observed. Conclusion Lung ultrasound has high accuracy, sensitivity, specificity, and repeatability in determining the position of bronchial blockers. It is a new and safe method to determine the position of bronchial blockers.